Responsibility and the ‘pie fallacy’ - Kaiserman, A (Springer, 2021)
Much of our ordinary thought and talk about responsibility exhibits what I call the ‘pie fallacy’—the fallacy of thinking that there is a fixed amount of responsibility for every outcome, to be distributed among all those, if any, who are responsible for it. The pie fallacy is a fallacy, I argue, because how responsible an agent is for some outcome is fully grounded in facts about the agent, the outcome and the relationships between them; it does not depend, in particular, on how responsible anyone else is for that same outcome. In this paper, I explore how the pie fallacy can arise by considering several different kinds of case in which two or more agents are responsible for the same outcome. I’ll end with some brief remarks on the potential consequences of my arguments for how to think about responsibility in war.